2017
DOI: 10.1186/s13673-017-0091-8
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and evaluating the behavior of technical users. A study of developer interaction at StackOverflow

Abstract: This paper is focused on analyzing the details of one of the most widely used Q&A technical discussion forums on the Internet: StackOverflow. StackOverflow is a huge source of information for both academics and industry practitioners and its analysis can provide useful insights. This is evident by a growing body of work dedicated to the study of this platform. There are several papers that have taken the ‘platform’ as an analyzing point to gain a few useful insights into the practices adopted by software d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Furtado, Oliveira, and Andrade (2014) summarized contributors into four types and proved that the majority of contribution in the communities are provided by activists and experts. Ahmed and Srivastava (2017) analysed the humanistic point of view of technical users and investigated the factors like locality and gender that play important role in CQA. The finding also showed that malpractices such as plagiarism were also common on Stack Overflow.…”
Section: Related Workmentioning
confidence: 99%
“…Furtado, Oliveira, and Andrade (2014) summarized contributors into four types and proved that the majority of contribution in the communities are provided by activists and experts. Ahmed and Srivastava (2017) analysed the humanistic point of view of technical users and investigated the factors like locality and gender that play important role in CQA. The finding also showed that malpractices such as plagiarism were also common on Stack Overflow.…”
Section: Related Workmentioning
confidence: 99%
“…There have been many works on knowledge discovery from Stack Overflow data [10], [20], [22], [5], [2] -from gamification motivation for voluntary contributions [5], discussion interest trend [20] to developer interaction [2] and repair patterns from extracted code samples [22]. However, most of these works have focused in Stack Overflow semantics and users behavior but rarely addressed the issue of code security analysis.…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, those women who do have a user account typically post less questions and answers as well as having shorter active careers on the platform and achieving lower maximum reputation scores. One possible explanation for the continued underrepresentation of women on Stack Overflow that has been argued for is based on a general sociological assumption that people often interact more with those of their own gender [21,22]. While this argument could account for lower per capita levels of interaction in the form of questions, answers and comments for women, it does not account for the very low proportion of accounts [18] that have been identified as belonging to women.…”
Section: Introductionmentioning
confidence: 99%